Expanding the applicability of FDM-type technologies through materials development. Issue 2 (16th March 2015) - Roberson, David; Shemelya, Corey M; MacDonald, Eric; Wicker, Ryan
Abstract : Purpose: – The purpose of this paper is to demonstrate the strategy for increasing the applicability of material extrusion additive manufacturing (AM) technologies, based on fused deposition modeling (FDM), through the development of materials with targeted physical properties. Here, the authors demonstrate materials specifically developed for the manufacture of electromechanical and electromagnetic applications, the use of FDM-type processes in austere environments and the application of material extrusion AM. Design/methodology/approach: – Using a twin screw polymeric extrusion process, novel polymer matrix composites and blends were created where the base material was a material commonly used in FDM-type processes, namely, acrylonitrile butadiene styrene (ABS) or polycarbonate (PC). Findings: – The work presented here demonstrates that, through targeted materials development, the applicability of AM platforms based on FDM technology can be increased. Here, the authors demonstrate that that the physical properties of ABS and PC can be manipulated to be used in several applications such as electromagnetic and X-ray shielding. Other instances of the development of new materials for FDM led to mitigation of problems associated with the process such as surface finish and mechanical property anisotropy based on build orientation. Originality/value: – This paper is an overview of a research effort dedicated to increasing the amount of material systems available to material extrusion AM. Here materials development is shown to not only increase the number of suitable applications for FDM-type processes, but to be a pathway toward solving inherent problems associated with FDM such as surface finish and build orientation-caused mechanical property anisotropy.